2016
DOI: 10.1039/c6ob01636g
|View full text |Cite
|
Sign up to set email alerts
|

Solid-phase synthesis and fluorine-18 radiolabeling of cycloRGDyK

Abstract: Solid-phase peptide synthesis, head-to-tail cyclization, and subsequent radiolabeling provided a reproducible, simple, rapid synthetic method to generate the cyclic peptide radiotracer cRGDyK([18F]FBA). Herein is reported the first on-resin cyclization and 18F-radiolabeling of a cyclic peptide (cRGDyK) in an overall peptide synthesis yield of 88% (cRGDyK(NH2)) and subsequent radiolabeling yield of 14 ± 2% (decay corrected, n = 4). This approach is generally applicable to the development of an automated process… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 42 publications
1
7
0
Order By: Relevance
“…Altogether, results indicate that the best synthetic route for the preparation of this specific head‐to‐tail cyclic peptide is the one depicted in Scheme , whereby the fully protected cyclic peptide is generated on a 2‐chlorotrityl‐chloride resin. The yield after purification and lyophilization was comparable with that reported in previous works by Hassert et al (31%) and Davis et al (46%), as well as the one reported, only analytically, by Del Gatto et al (66%, using NovaSyn TGA by Novabiochem) for the preparation of the analogue c [RGDfK].…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…Altogether, results indicate that the best synthetic route for the preparation of this specific head‐to‐tail cyclic peptide is the one depicted in Scheme , whereby the fully protected cyclic peptide is generated on a 2‐chlorotrityl‐chloride resin. The yield after purification and lyophilization was comparable with that reported in previous works by Hassert et al (31%) and Davis et al (46%), as well as the one reported, only analytically, by Del Gatto et al (66%, using NovaSyn TGA by Novabiochem) for the preparation of the analogue c [RGDfK].…”
Section: Resultssupporting
confidence: 89%
“…Most methods also suffer the racemization of the C‐terminal residue or aspartimide formation, and formation of tetramethyl‐guanidinium derivatives . To partly overcome these problems, the solubility difficulties often encountered with fully protected peptides and to avoid lengthy intermediate purifications, on‐resin cyclisation and lysine functionalization approaches have been devised and reported . However, even if solid‐phase cyclisation has represented a step forward compared with the one in solution to circumvent cyclo‐dimerization and/or oligomerization side reactions, it does not always completely solve the problem .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[50][51][52][53][54][55] The yield obtained for cRGDyK([ 18 F]FPy) was also similar to the previously reported manual solid phase radiolabeling of cRGDyK with 6-[ 18 F]uorobenzoic acid (14 AE 2% yield in 90 minutes). 42 Overall, using the ELIXYS FLEX/CHEM® radiosynthesizer was faster, with a total synthesis time under a 100 minutes including HPLC purication, and provided similar radiochemical yields.…”
Section: Discussionmentioning
confidence: 91%
“…All peptides were radiolabeled with [ 18 F]fluorobenzoic acid ([ 18 F]FBA) on resin following our well-established solid-phase radiolabeling protocols [16,20,37]. Briefly, [ 18 F]fluoride was reacted with ethyl-4-(trimethylammonium triflate)benzoate in the presence of 4,7,13,16,21,24-hexaoxa-1,10-diazabicyclo [8.8.8]hexacosane (Kryptofix TM [K2.2.2], (Sigma Aldrich, St. Louis, MO, USA) and potassium carbonate at 100 °C in dimethylsulfoxide (DMSO) for 15 min, followed by saponification of the ethyl ester protect group to yield [ 18 F]FBA.…”
Section: Methodsmentioning
confidence: 99%